FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN GANGGUAN PERNAPASAN PADA PEKERJAPT. MATAHARI INDONESIA TIMUR (MIT) KOTA BAUBAU - AGUS DARMAWAN; Waode Nurfadilah; Eky Endriana Amiruddin (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2023)
To workers at PT. Matahari of Eastern Indonesia (MIT) Baubau City has any health complaints during their work, namely shortness of breath, coughing, sneezing, and even feeling easily tired. This is thought to be due to workers not using PPE in the form of masks so that exposure to dust at work is inhaled by workers. The purpose of the study is Factors Related to Respiratory Distress Complaints in workers PT MIT Baubau City. The type of research used is quantitative research with a cross sectional study research design. The population is 32 workers with a sample size of 32 workers. Sample withdrawal techniques are used total sampling with analsis data used the chi schquare test with a confidence level of 95%. The results of the study obtained the relationship of working period with respiratory disorders obtained the result of the value of p = 0.024 < the value of α = 0.05. The relationship of knowledge with respiratory disorders is obtained results with a value of p = 0.012 < a value of α = 0.05. The relationship between PPE use and respiratory disorders was obtained with a value of p = 0.001 < a value of α = 0.05. Conclusions in the study, namely there is a relationship of working period, knowledge and use of PPE with Respiratory Disorders in workwes of PT. MIT Baubau City. It is recommended to workers to use personal protective equipment in the form of masks during work every day.